2019
DOI: 10.1074/jbc.ac119.009198
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–liquid phase separation of tau protein: The crucial role of electrostatic interactions

Abstract: Recent studies have indicated that tau, a protein involved in Alzheimer's disease and other neurodegenerative disorders, has a propensity to undergo liquid–liquid phase separation (LLPS). However, the mechanism of this process remains unknown. Here, we demonstrate that tau LLPS is largely driven by intermolecular electrostatic interactions between the negatively charged N-terminal and positively charged middle/C-terminal regions, whereas hydrophobic interactions play a surprisingly small role. Furthermore, our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
192
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 181 publications
(227 citation statements)
references
References 34 publications
19
192
0
Order By: Relevance
“…Consistent with previously published data (15), in the absence of any crowding agents, freshly prepared solution of tau441 (10 µM) at neutral pH in 10 mM HEPES buffer (pH 7.4) containing 10-150 mM NaCl shows no measurable turbidity, indicating that the protein exists in a single phase, most likely as a monomer (21). However, upon addition of Zn 2+ (40 µM) to the protein solution at low ionic strength (10 mM HEPES, 10 mM NaCl, pH 7.4), a large increase in turbidity was observed ( Fig.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with previously published data (15), in the absence of any crowding agents, freshly prepared solution of tau441 (10 µM) at neutral pH in 10 mM HEPES buffer (pH 7.4) containing 10-150 mM NaCl shows no measurable turbidity, indicating that the protein exists in a single phase, most likely as a monomer (21). However, upon addition of Zn 2+ (40 µM) to the protein solution at low ionic strength (10 mM HEPES, 10 mM NaCl, pH 7.4), a large increase in turbidity was observed ( Fig.…”
Section: Resultssupporting
confidence: 90%
“…The previous study (15) (performed using similar experimental conditions but a more potent crowding agent, PEG 10) revealed that, in the absence of zinc, the N-terminally truncated tau441 variants Δ1-243 and Δ1-117 as well as the K18 fragment lost the ability to undergo LLPS, whereas the propensity of the Δ2N and Δ4R variants for LLPS was diminished (but not completely abrogated), as indicated by the requirement for higher concentrations of the crowding agent compared with that for tau441. This, together with data shown herein in Fig.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The findings of this study showcase how GRNs -3 and -5 modulate the dynamics of TDP-43CTD in forming insoluble aggregates or SGs in both oxidizing and reducing conditions. It is clear from the data that GRN-3 and GRN-5 affect TDP-43CTD aggregation via disparate mechanisms; while GRN-3 induces the formation of insoluble inclusions, GRN-5 coacervates with TDP-43CTD to undergo LLPS in both reduced and oxidized forms an interaction which is likely to be driven by the counter-ionic electrostatic characteristics of TDP-43CTD and the negatively charged GRN-5 which are known to be common mediators of LLPS (85)(86)(87). Furthermore, GRN-3 and GRN-5 also disrupt SGs formed by RNA and TDP-43CTD.…”
Section: Discussionmentioning
confidence: 99%